Pengaruh PDRB Per Kapita, Indeks Pembangunan Manusia, dan Tingkat Partisipasi Angkatan Kerja Terhadap Ketimpangan Distribusi Pendapatan di Indonesia - Aprillia Nilasari; Rizky Amelia (Inspirasi Nusantara, 2022)
Income inequality has long been a serious problem in most developing countries. In Indonesia, many regions still have inequality problems in their income distribution. Income inequality means that there is inequality in income distribution which results in differences in people's economic conditions due to many factors. This research was conducted to determine the effect of GRDP per capita, the human development index, and the labor force participation rate on income distribution inequality in Indonesia in 2019-2021. This quantitative research uses secondary data from 34 provinces in Indonesia in the form of time series data for 2019 - 2021. The results of this study indicate that GRDP per capita and HDI significantly positively affect income distribution inequality. In contrast, the labor force participation rate negatively and significantly affects income distribution inequality.